Insecticides advertisements: strategies for minimization and concealment of household risks - Castro, Jane Silva Maia; Rozemberg, Brani (Saúde e Sociedade, 2015)
The study aims to analyze and propose a discussion on insecticide ads for domestic use and their implications on public health. We analyzed insecticide ads broadcast on the television between the years of 2008 and 2010. As selection criteria four insecticide ads were chosen, which aired on two television channels, in the morning and in the evening, over that period. The ads were analyzed by watching their broadcast on television. The method used was content analysis. The categories generated by the analysis were: appeal to the user's status; concealment and downscaling of risks; symbols of modernity and rationality; representations of an aseptic world; and representations of strength, power and control. We, therefore, conclude that all the evaluated ads adopted strategies that concealed the risks of domestic insecticides and did not comply with Brazilian legislation.